2021
DOI: 10.1136/bmjsem-2021-001135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of insufficient physical activity among elderly people in Bangladesh: a nationally representative cross-sectional study

Abstract: ObjectivesInsufficient physical activity (IPA) is a crucial risk factor for non-communicable diseases (NCDs). The elderly population has a higher likelihood of suffering from NCDs. We aimed to estimate the prevalence of and factors associated with IPA among the elderly people in Bangladesh.MethodsWe analysed data from the Bangladesh Food Security and Nutrition Surveillance round 2018–2019, collected from 82 rural, non-slum urban and slum clusters selected using multistage cluster sampling. IPA was defined as &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another prominent factor for overweight is physical inactivity [19]. The level of physical inactivity in Bangladesh is unclear, a scoping review indicated a range between 5% and 83% [20], whereas a corresponding figure for the elderly is 40% [21]. However, a modern lifestyle is associated with increased sedentary behavior and is expected to contribute to the rising prevalence of overweight in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Another prominent factor for overweight is physical inactivity [19]. The level of physical inactivity in Bangladesh is unclear, a scoping review indicated a range between 5% and 83% [20], whereas a corresponding figure for the elderly is 40% [21]. However, a modern lifestyle is associated with increased sedentary behavior and is expected to contribute to the rising prevalence of overweight in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed in the literature [15,19,20] indicate that the older adults population still presents low levels of physical activity due to aging [11], which can create greater barriers for people living with NCD. Considering that these factors may remain interconnected with social inequality seen in different regions of Brazil [21], as well as access to healthcare services [19] and differences in race, education, and economic level, show significant relationships with the presence or worsening of NCD [18], causing difficulties for physical activity practice in these individuals, in addition to the limitations already present due to NCD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regular physical activity is associated with multiple health benefits, such as improved physical and mental function, prevention and reduction in the progression of NCD, increased years of life, and better quality of life [7][8][9][10], although these levels of physical activity tend to decrease with advancing age as it is a natural process [11].…”
Section: Introductionmentioning
confidence: 99%